Estudo químico e avaliação biológica de Phanera glabra (Jacq.) Vaz & Bauhinia ungulata L. (FABACEAE) - Sousa, Leôncio Mesquita de (2016)
This paper describes the chemical and biological study of species Phanera glabra (Jacq.) Vaz and Bauhinia ungulata L. The chemical composition of essential oil from leaves of B. ungulata, obtained by hydrodistillation, was analysed by gas chromatography-mass spectroscopy (GC-MS) and gas chromatography-flame ionization detector. Twenty-two constituents were identified representing 85.90% of the total composition: Caryophyllene oxide (22.99%), (E)-caryophyllene (14.53%) and α-copaene (7.17%) were the major constituents. Larval bioassay against Aedes aegypti of B. ungulata essential oil showed LC50 value of 75.12 ± 2.82 µg/mL. The cytotoxic effect against four human tumor cell lines HL-60, MCF-7, NCI-H292 and HEP-2 was evaluated, showing IC50 values of 10.57; 22.25; 23.11 and 26.56 µg/ mL, respectively. The study of the non-volatile constituents was initiated with the preparation of the hexane and ethanol extracts from stems of P. glabra. The chromatographic fractionation of these extracts allowed the isolation of lupenone (PG–1), the mixture of sitosterol and stigmasterol (PG–2), 4'-hydroxy-7- methoxyflavone (PG–3), 3',7-dimethoxy-4'-hydroxyflavone (PG–4) and 5,5'- dihydroxy-2',3,7-trimethoxyflavone (PG–5). Taraxerol (BU–1), betulinic acid (BU–2), taraxerone (BU–3), glutinol (BU–4), the mixture of sitosterol and stigmasterol (BU–5), pacharin (BU–6), naringenin (BU–7) and eriodictyol (BU–8), liquiritigenin (BU–9), guibourtinidol (BU–10) and fisetinidol (BU–11) were obtained from the extracts from stems of B. ungulata; while 3,5-dimethoxy-4-methyl-2’-hydroxybibenzyl (BU–12) and 3,5-dimethoxy-2’-hydroxybibenzyl (BU–13) were isolated from the ethanol extract of the roots. The structures of the compounds were elucidated by spectroscopic methods as IR, MS, 1D and 2D NMR, and by comparison with previously reported data in the literature. It's worth noting that BU–12 is unprecedented in the literature and the 13C NMR data of BU–13 are reported for the first time in this work. The cytotoxicity of BU–12 has been evaluated against four human cancer cell lines, showing IC50 values of 4.3 and 6.5 µg/mL against pro-myelocytic leukemia (HL-60) and cervical adenocarcinoma (HEP-2) cell lines, respectively.